Astilbin Activates the Reactive Oxidative Species/PPARγ Pathway to Suppress Effector CD4+ T Cell Activities via Direct Binding With Cytochrome P450 1B1 - Ding, Shizhen; Lu, Guotao; Wang, Biying; Xiang, Jie; Hu, Chunxia; Lin, Zhijie; Ding, Yanbing; Xiao, Weiming; Gong, Weijuan (Frontiers in Pharmacology, 2022)
Astilbin, as a compound of flavonoids, exerts anti-inflammation, antioxidation, and immune-suppression activities. Decreased activation of NF-κB and p38 MAPK and increased activation of SOCS3 and AMPK have been found in astilbin-treated cells. However, what molecules are docked by astilbin to initiate signaling cascades and result in functional changes remains unknown. In the study, we found that astilbin efficiently suppressed TNF-α production and increased CCR9 and CD36 expression of CD4+ T cells. In vivo administration of astilbin repressed the occurrence of type 1 diabetes mellitus in non-obese diabetic mice. The PPARγ/SCOS3, PPARγ/PTEN, and PPARγ/AMPK signaling pathways were substantially activated and played key roles in astilbin-induced downregulation of CD4+ T cell functions. Transcriptome sequencing results confirmed the changes of signaling molecules involved in the immune system, inflammatory responses, and indicated variations of multiple enzymes with oxidant or antioxidant activities. Astilbin directly induced cytoplasmic ROS production of CD4+ T cells ex vivo, but had no effects on mitochondrial ROS and mitochondrial weight. When cellular ROS was depleted, astilbin-treated CD4+ T cells remarkably reversed the expression of TNF-α, IFN-γ, CCR9, CD36, and signaling molecules (PPARγ, PTEN, p-AMPK, and SCOS3). Based on bioinformatics, two P450 enzymes (CYP1B1 and CYP19A1) were selected as candidate receptors for astilbin. CYP1B1 was identified as a real docking protein of astilbin in ROS production by AutoDock Vina software analysis and surface plasmon resonance assay. Collectively, astilbin downregulates effector CD4+ T cell activities via the CYP1B1/ROS/PPARγ pathway, which firmly supports its potential use in the treatment of inflammation.